Characteristics of Soil Layers Based on Cone Penetration Test (CPT) for a Planned Villa Development (Case Study: Cisarua, Bogor) - Evan Febri Miranda; Respati Anton Sasongko; Mirnanda Cambodia; Dian Pratiwi (Journal of Civil Engineering and Planning (JCEP), 2025)
The planned villa development in the hilly area of Cisarua, Bogor, requires a comprehensive geotechnical study to ensure the safety and reliability of the building foundations. This study aims to identify soil layer characteristics, determine soil consistency, and evaluate the allowable bearing capacity of shallow and deep foundations based on Cone Penetration Test (CPT) results at three investigation points. Primary data consist of cone resistance (qc) and total sleeve friction (Tf) measured at 20 cm depth intervals, which are then interpreted to obtain the stratigraphic soil profile, in-situ soil classification using qc and friction ratio (fr), as well as the calculation of allowable bearing capacity using the L. Herminier approach for shallow foundations and the Meyerhof method for deep foundations. The results indicate that soft to firm soil layers are found at shallow depths, while hard soil layers with qc values of about 250 kg/cm² occur at depths of 24–25 m, which are suitable as the main bearing layer for deep foundations. The allowable bearing capacity of shallow foundations at depths of 1.0–2.0 m ranges from approximately 1.9 to 12.0 ton/m², making them suitable only for light structures with careful settlement control, whereas for heavier structures, pile foundations extending to the hard layer are recommended, supported by static load tests and, if necessary, additional deep boring and SPT investigations.​